Posture and musculoskeletal pain in eutrophic, overweighed, and obese students. A cross-sectional study - Mariana Vieira Batistão; Leticia Carnaz; Luis Felipe Barbosa; Gislaine Cristina da Motta; Tatiana de Oliveira Sato (Universidade Estadual Paulista (UNESP), 2014)
Childhood obesity increases susceptibility to musculoskeletal injuries. The purpose of this study was to describe the prevalence of overweight and obesity and to identify differences in posture and musculoskeletal pain among eutrophic, overweight, and obese students. Participants were 420 students, 252 (60%) were females and 168 males (40%), with a mean age of 11.1 (±2.3) years. The posture of all participants was qualitatively assessed; the quantitative postural evaluation was performed using the Postural Assessment Software (PAS/SAPo) for a population subsample of 99 participants. An adapted version of the Nordic Musculoskeletal Questionnaire was used for pain assessment. Data were analyzed descriptively and via statistical tests (significance level of p<0.05). The target population exhibited 22.1% of overweight individuals and 14.1% of obese. Compared to the eutrophic students, the postural evaluation showed a higher knee valgus angle, higher incidence of thoracic kyphosis, and greater prevalence of lumbar hyperlordosis in overweight and obese students (p≤0.05). No association between overweight and pain complaints was detected (p=0.994).